2014
DOI: 10.1371/journal.pone.0097570
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular Basis of Impaired Glycogen Metabolism during Ischemic Stroke and Hypoxia

Abstract: BackgroundIschemic stroke is the combinatorial effect of many pathological processes including the loss of energy supplies, excessive intracellular calcium accumulation, oxidative stress, and inflammatory responses. The brain's ability to maintain energy demand through this process involves metabolism of glycogen, which is critical for release of stored glucose. However, regulation of glycogen metabolism in ischemic stroke remains unknown. In the present study, we investigate the role and regulation of glycoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 61 publications
0
18
0
Order By: Relevance
“…Brain glycogen has long been considered as an emergency glucose store that provides neuronal protection during stress episodes, including hypoglycemia and hypoxic stress (3)(4)(5)7). Over the past years, increasing interest has been paid to brain glycogen as it is also critical in normal brain functions and high cognitive processes, in particular by providing lactate and energy for the astrocyte-neuron lactate shuttle (8,9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brain glycogen has long been considered as an emergency glucose store that provides neuronal protection during stress episodes, including hypoglycemia and hypoxic stress (3)(4)(5)7). Over the past years, increasing interest has been paid to brain glycogen as it is also critical in normal brain functions and high cognitive processes, in particular by providing lactate and energy for the astrocyte-neuron lactate shuttle (8,9).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been shown that oxidative stress and redox conditions in astrocytes could impact glycogen mobilization (3,7,27). As both mGP and bGP are expressed in the brain (in particular in astrocytes), we first tested whether bGP and mGP activity could be inhibited by H 2 O 2 .…”
Section: Human Bgp Is Reversibly Inhibited By Bolus Addition and Bymentioning
confidence: 99%
“…153 Interestingly, the astrocyte's glycogen stores and the presence of a high amount of metallothionein (MT), glutathione, and other antioxidants protect the surrounding tissues from hypoglycemic and hypoxic ischemic shock. [160][161][162] Microglia Microglia (CD45 low , CD68 + , Iba1 + ) are mononuclear resident phagocytic macrophages of normal brain originated from myeloid stem cells in the yolk sac. 163,164 The main functions of microglia are to offer immune protection of the brain, a clean brain microenvironment via phagocytosis of unwanted debris, support of other glial cells and neurons, and aid in BBB and synaptic plasticity maintenance.…”
Section: Role Of Neurovascular Unit In Ischemia and Glioma Astrocytesmentioning
confidence: 99%
“…His 6 Tag Cleavage by Thrombin Digestion-The His 6 tag was removed by thrombin digestion. Briefly, 20 mg of 6xHis-bGP was incubated with biotinylated-thrombin (0.5 units thrombin/mg protein, purchased from Merck-Millipore) for 3 h on ice.…”
Section: Purification Of Recombinant Bgp From E Coli-extractionmentioning
confidence: 99%